STUDY OF VERNACULAR SOLAR PASSIVE DESIGN TECHNIQUES FOR COLD AND DRY CLIMATE LADAKH - Gautam, Ashish; Atreya, Sonal; Kumar K, Anil (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Ladakh, one of the remote regions in the Himalayas, has been an example of a self-sustainable ecosystem with its unique socio-economic and cultural characteristics since time immemorial. Primarily a rural agrarian economy, all social activities and basic life processes were sustainably interlinked in a cordial community setup. The current study focuses on the vernacular passive design techniques of the dwelling units in Ladakh's cold and dry climate. The study aims to explore the vernacular passive design techniques of the Ladakh region by examining aspects related to spatial design, thermal mass, material usage, insulation, and other concepts that may be crucial for designing conventional buildings. Traditional dwelling units within the Ladakh region have been selected for the study purpose, and analysis has been conducted through qualitative methods like an observational approach, photographic analysis, and quantitative analysis. Along with the analysis, different construction elements of the dwelling units have been studied with respect to their performance. The study concludes with an overview of the revival strategies for vernacular passive design techniques that can be amalgamated into appropriate interventions on materials and passive design aspects in the contemporary scenario. The study thus adds to the existing knowledge base towards reviving vernacular architecture through an amalgamation of the vernacular and contemporary knowledge, which will be beneficial to building a sustainable environment.